2018
DOI: 10.22146/ijc.37050
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methylene Blue on the Composite Sorbent Based on Bentonite-Like Clay and Hydroxyapatite

Abstract: The adsorption of methylene blue from model aqueous solutions on bentonite-like clay, hydroxyapatite, and a composite sorbent has been investigated. The kinetic and thermodynamic parameters of adsorption in the temperature range 298–333 К have been calculated. The process is found to obey Langmuir isotherm equation. It is spontaneous but slightly endothermic. The maximal sorption capacity of the composite sorbent toward methylene blue is 175.4 mg/g at 25 °С that is 1.3 times more than that for bentonite-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
(36 reference statements)
2
19
0
2
Order By: Relevance
“…The Qm values, which represents the maximum adsorption capacity for RB and MB, are 97.08 and 128.21 mg/g, respectively. This MB adsorption capacity is quite higher than other reported adsorbent materials such as hydroxyapatite with an adsorption capacity of 9.88 mg/g [25], mordenite (37.362 mg/g) [41], but it is lower than bentonite (136.98 mg/g) [25]. Turning to the rhodamine B, the adsorption capacity in this works is higher than mordenite (3.61 mg/g) [23], montmorillonite (42.19 mg/g) [42] and bentonite (98.62 mg/g).…”
Section: Adsorption Isothermmentioning
confidence: 57%
See 2 more Smart Citations
“…The Qm values, which represents the maximum adsorption capacity for RB and MB, are 97.08 and 128.21 mg/g, respectively. This MB adsorption capacity is quite higher than other reported adsorbent materials such as hydroxyapatite with an adsorption capacity of 9.88 mg/g [25], mordenite (37.362 mg/g) [41], but it is lower than bentonite (136.98 mg/g) [25]. Turning to the rhodamine B, the adsorption capacity in this works is higher than mordenite (3.61 mg/g) [23], montmorillonite (42.19 mg/g) [42] and bentonite (98.62 mg/g).…”
Section: Adsorption Isothermmentioning
confidence: 57%
“…This Langmuir adsorption is in good accordance with the isothermal adsorption type reported by several researchers. Vezensev et al [25] reported in his findings that the adsorption of MB in bentonite-like clay and hydroxyapatite also followed the Langmuir model. The more recent findings reported by Santosa et al [26] also shows the same result.…”
Section: Adsorption Isothermmentioning
confidence: 88%
See 1 more Smart Citation
“…Adsorption method appeared as the best technique among various dye removal techniques due to its good performance in the removal of different types of coloring materials [2,[4][5]. Regarding the adsorbent material, activated carbon has been commercially used for adsorption process owing to its excellent adsorption ability [6][7].…”
Section: ■ Introductionmentioning
confidence: 99%
“…В последние годы проводятся исследования, направленные на очистку воды и почвы от соединений тяжелых металлов с использованием не только традиционных, хорошо известных сорбентов, таких как активные угли, но и доступных природных материаловминеральных алюмосиликатных адсорбентов (глины, цеолитсодержащие породы и т.д.) [5][6][7][8][9][10].…”
Section: Introductionunclassified